2019
DOI: 10.18535/jmscr/v7i9.13
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Antepartum Hemorrhage and Its Maternal and Perinatal Outcome at Tertiary Care Hospital in Western Rajasthan

Abstract: Background: Antepartum hemorrhage is an obstetric emergency contributing to a significant amount of perinatal & maternal morbidity and mortality. The main causes of APH are placenta previa, abruptio placentae, indeterminate cause or local causes of genital tract. APH complications can be fetal as well as maternal. The maternal complications are malpresentation, premature labor, postpartum hemorrhage, sepsis, shock and retained placenta. Various fetal complications are prematurity, low birth weight, intrauterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
8
9
0
Order By: Relevance
“…From the literature review, Yadav et al 4 reported in their study that 25-29 years' age were commonest age group in their study which was quite similar to our study. In their study, placenta praevia, abruptio placentae and unclassified variety were 76.8%, 20.5% and 2.7% respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…From the literature review, Yadav et al 4 reported in their study that 25-29 years' age were commonest age group in their study which was quite similar to our study. In their study, placenta praevia, abruptio placentae and unclassified variety were 76.8%, 20.5% and 2.7% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Yadav MC et al 4 found neonatal jaundice was present in 26.8% of APH but among the women of placenta praevia it was present in each (30/30) new-born. Their findings were contradictory with the finding of our study, that may be due to study conducted in different geographical locations, or may be due to there was small sample size.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar results were seen in study conducted by Yadav et al in 2019 which shows 76.8% cases were of placenta previa followed by 20.5% cases of abruptio placenta and rest 2.7% cases were unclassified. 9 In our study 86% of the patients were below 30 years age, which was similar to the result reported by Sharma et al and Rajoriya et al in which the 72% and 51.2% cases of APH were belonged to aged 26-30 years. 10,11 Similar results were reported by Das et al, Abbasi et al also reported the mean age 30 years.…”
Section: Discussionsupporting
confidence: 91%